Team idiosyncratic deals and team breakthrough innovation: Based on the perspective of input-process-output model - Fan, Zili; Sun, Hao; Wang, Lijun; Zhu, Mengting; Peng, Ting (Frontiers in Psychology, 2022)
Purpose As a new human resource management practice, idiosyncratic deals are personalized employment arrangements negotiated between employees and employers and intended to benefit them both. It plays an important role in attracting, retaining and motivating employees to promote breakthrough innovation. Based on the input-process-output (I-P-O) model, this paper examines the relationship between team idiosyncratic deals and team breakthrough innovation, the mediating role of team exploratory-exploitative knowledge sharing, and the moderating roles of team transactive memory systems and team cognitive flexibility. Participants and methods In order to reduce the effects of common method biases and causal lag effect, this study is divided into three stages for data collection, with a time interval of 1 month. Eighty teams (406 employees) from six enterprises in Shanghai and Hangzhou were selected as samples, and the hypothesis test was carried out by hierarchical regression analysis, bootstrap, and Johnson-Neyman method. Results The results show that higher team idiosyncratic deals are associated with higher team breakthrough innovation through higher team exploratory-exploitative knowledge sharing, and that team transactive memory systems and team cognitive flexibility positively moderate the mediating effect of team exploratory-exploitative knowledge sharing in the relationship between team idiosyncratic deals and team breakthrough innovation in the first stage and the second stage, respectively. Under the joint effect of high team transactive memory systems and high team cognitive flexibility, the mediating effect of team exploratory-exploitative knowledge sharing is stronger. Conclusion The research results break through the previous research framework of social exchange theory, and I-P-O model to explore the influence mechanism of team idiosyncratic deals, in order to promote the sustainable growth of team breakthrough innovation through this non-standard work arrangement. It is hoped that this research can inspire modern enterprises to create team idiosyncratic deals for valuable teams engaged in breakthrough innovation, which are more conducive to give full play to their heterogeneous talents, and finally help enterprises break through the industry bottleneck and win the market competition.